Literasi Budaya : Upaya Meningkatkan Mutu Pendidikan di Sekolah Dasar - Nandia Kiranti; Dinie Anggraeni Dewi; Rizky Saeful Hayat (Jurnal Multidisiplin Indonesia, 2023)
The School Literacy Movement is a comprehensive effort to make schools into learning organizations whose citizens are literate throughout life. Basic education institutions, especially elementary schools, have a very important role in building a generation that is ready to face various challenges. Cultural Literacy is the ability to understand and behave towards Indonesian culture as a national identity. This type of research is descriptive research with a qualitative approach method. The data collection technique used in this research is through library research or literature study with reference sources from books, journals, research report articles and sites on the internet. The results of this research can be said that cultural literacy greatly influences improving the quality of education in elementary schools.